PENERAPAN MODEL PEMBELAJARAN GROUP INVESTIGATION BERBANTUAN DIGITAL MIND MAP (GI-DMM) TERHADAP HASIL BELAJAR BIOLOGI SISWA SMAN 1 SUTERA FASE F - Yunda, Rahma yunda; Siska Nerita; Evrialiani rosba (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the low learning outcomes of students, during the implementation of learning teachers still tend to use discussion methods, lectures, questions and answers, and scientific approaches. Discussion activities that take place in the learning process have not gone well, because during discussion activities not all group members are involved in answering questions and completing assignments given by the teacher. This will have an impact on students' understanding of the material being studied. This study aims to determine the application of the Group Investigation learning model assisted by Digital Mind Map (GI-DMM) on the Biology learning outcomes of SMAN 1 Sutera Phase F students. This type of research is experimental research and the research design used is Randomized Control Group Pottest Only Design. The population in this study was all F FASE SMAN 1 Sutera in the even semester registered in the 2023/2024 academic year consisting of 9 classes with a total of 265 students. The sample determination was carried out using a purposive sampling technique, namely sampling based on certain considerations, the experimental class F FASE F1 and the control class F FASE F3. The formative assessment research instrument is assessed from the conclusion in the form of a digital mind map, and the summative assessment is assessed in the form of multiple choice questions in the form of a written test. The data analysis technique uses a hypothesis test (t-test). The results of the study on the formative assessment in the experimental class obtained an average value of 88.11 and the control class 80.88. Hypothesis testing using the t test obtained t count 2.89> t table 1.67, meaning that the Hypothesis (H1) is accepted. While in the summative assessment in the experimental class the average value is 62.5 and the control class 55.7. Hypothesis testing using the t test obtained t count 1.82> t table 1.67 meaning that the Hypothesis (H1) is accepted. From both assessments, the experimental class was higher than the control class. Thus, it can be concluded that through the application of the Group Investigation learning model assisted by Digital Mind Map (GI-DMM) can improve learning outcomes in the formative assessment and summative assessment of students at1 Pendas : Jurnal Ilmiah Pendidikan Dasar, ISSN Cetak : 2477-2143 ISSN Online : 2548-6950 Volume XX Nomor XX, Bulan TahunSMAN 1 Sutera, Pesisir Selatan Regency.Keywords: critical thinking, process skills approach, science learning.